University internationalization: multiple actors, policies and languages in interaction - Furtado Guimarães, Felipe (Revista Letras Raras, 2024)
This study aimed at building a language policy (LP) model that sought to promote more democratic language practices to support the internationalization of higher education institutions (HEIs) in Brazil, considering mainly the issues of governance and decision-makers in LP. To this end, bibliographic research was carried out focusing on decision-makers (indicated here as political actors/agents, as they act in matters of policy design, implementation and evaluation) and governance issues, considering the policy cycle discussed by Ball (2019) and highlighted by Gimenez (2013), as well as topics related to language policies in general, internationalization and multilingualism. A survey was also used, in which institutions that are part of the Capes PrInt program (institutional internationalization program), established in 2017, participated. Results suggest that the following aspects should be considered when designing language policies for Brazilian HEIs with a view to internationalization processes: multiple actors and levels; policy interpretation; policies as textual interventions; capacity for agency; relations between actors; and policy negotiation. This way, it is expected that (by adopting these aspects) language practices will be more democratic in university contexts impacted by internationalization processes.